PENANAMAN NILAI KARAKTER MELALUI KEGIATAN EKSTRAKURIKULER PENDIDIKAN PRAMUKA DI SEKOLAH DASAR - Panida Nurfazira; Faizal Chan; Hendra Budiono (Jurnal Tunas Pendidikan, 2026)
ABSTRACT This research aims to describe in more depth the process of implementing responsibility and discipline character education as well as the supporting factors for achieving the cultivation of character values through extracurricular scout education at state elementary school 212/IV, Jambi City. This research was conducted at state elementary school 212/IV, Jambi City in November 2023. This research used qualitative research methods with a phenomenological type of research. Research data was obtained by interviewing supervisors, school principals, students and their parents. After obtaining the interview results, the data was analyzed qualitatively. The results of the research show that the implementation of extracurricular activities in the context of instilling character values is effective in various attitudes or characteristics of students, especially in the character of responsibility and discipline. This was achieved due to the seriousness of the coaches in instilling character education in students where the coaches themselves were very competent and certified. Thus, the cultivation of character values is also supported by the school principal providing adequate and sufficient facilities and infrastructure to be used during each training session. From the results of this research, instilling character values through scout extracurricular activities at SD Negeri 212/IV Jambi City has been achieved well with the supporting factors of adequate facilities and infrastructure, support from the school principal or kamabigus, certified and competent scout leaders and support from the participants' parents. educate.